Assessment of hydrological response of Pahang river basin - Hakim, Nur Wajihah; Salleh, Md Noor; Al Mamun, Abdullah; Ali, Maisarah; Ayob, Mohd Fairullazi; Sekaran, Thayalam; Ismail, Mohd Azmi; Mat Amin, Mohd Zaki (Brunei, 2021)
Flooding is one of Malaysia's most common natural disasters, particularly during the northeast monsoon season, which happens in November until March every year. It is estimated about 33,298km2 of Malaysia is flood-prone, that affecting 21% of population based on report from DID Malaysia. Most of the flood mitigation are focuses on structural mitigations but non-structural flood control are also very necessary. Besides it is easier to implement and less expensive. One of the many non-structural flood management approaches is flood modelling. It involves simulation of flood events in a computer to predict the peak water level and further possible inundation area of the study area. It is the first step towards understanding and managing flood behavior. The study is carried out to focus on performing non-structural mitigation in Pahang River Basin. This paper focuses on the primary data collection which involves on the hydrological data that are suitable to be analyzed.